STRATEGI KREATIF DIVISI VIDEO DALAM PEMBUATAN KONTEN IKLAN DI SIGNOMIC CREATIVE AGENCY - Venska Abrar Pratisto (Solidaritas, 2025)
ABSTRACT This study aims to analyze the creative strategy design process of the Video Division in producing advertising content at Signomic Creative Agency, focusing on the implementation of the creative brief and storytelling. The research method employed is descriptive qualitative, with data collected through interviews, observations, and documentation. The findings indicate that the creative strategy is carried out through three main stages: pre-production, production, and post-production. In the pre-production stage, the creative brief serves as a strategic guide to define communication objectives, target audiences, key messages, and visual references compiled into a creative deck, script, and storyboard. The production stage focuses on executing the concept through shooting consistent with the designed storytelling, maintaining narrative continuity, and ensuring cross-division coordination. The post-production stage involves visual editing, audio adjustments, adding graphic elements, and revisions based on team and client feedback, with storytelling preserved to reinforce brand messages. The study concludes that the success of creative strategies at Signomic is determined by cross-division collaboration, the use of the creative brief as a framework, and relevant storytelling, as well as content format adaptation to suit the characteristics of digital platforms. These findings can serve as a reference for the creative industry in optimizing the role of video divisions to produce effective and impactful advertising content. Keywords: creative strategy, video division, advertising, pre-production, production, post-production, creative brief, storytelling